The Application Of The Discovery Learning Model In Improving Early Childhood Cognitive Development - Septinia Lae; Risna Bureni; Inka Nenometa; Elda Haekase; Riwanti Sio; Habel Lauren; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Background: Cognitive development is a fundamental aspect of early childhood education because it supports children's ability to think, understand concepts, and solve problems. Although many studies have reported the effectiveness of Discovery Learning, limited evidence has examined its implementation using an ex post facto design in authentic classroom settings. Objective: This study aimed to examine the effect of the Discovery Learning method on the cognitive development of children aged 5–6 years at TK Cemara Liliba, Kupang City. Method: A quantitative approach with an ex post facto design was employed involving 18 children selected through total sampling. Data were collected using Discovery Learning and cognitive development scales based on Bruner's learning theory and Piaget's cognitive development theory and analyzed using descriptive statistics and simple linear regression. Results: Discovery Learning had a positive and significant effect on children's cognitive development, with an R Square value of 0.286, indicating a contribution of 28.6%. The mindful, meaningful, and joyful dimensions also supported children's active engagement during learning. Novelty: This study provides empirical evidence of the effectiveness of Discovery Learning using an ex post facto design in an authentic classroom context. Conclusion: Consistent implementation of Discovery Learning can enhance children's cognitive development and provide practical guidance for teachers in designing exploration-based learning activities.